Формування фінансової стратегії підприємства - Латишева, І. Л.; Шамарина, В. В. (НТУ "ХПІ", 2014)
В статті визначені основні проблеми щодо формування фінансової стратегії підприємства в умовах становлення та розвитку економіки знань. Визначено необхідність визначення сучасного засобу формування фінансової стратегії підприємства. Реалізація запропонованого засобу відбувається завдяки побудованій стратегічній карті, яка реалізує фінансову стратегію через чотири проекції. За допомогою карти можна регулювати обрану фінансово стратегію використовуючи збалансовану систему показників.

In the article the basic problems of the development of financial strategy of the enterprise in terms of formation and development of the knowledge economy and methodological approaches to the management of financial strategy on grounds strategy maps. Formation of financial strtatehiyiyi company provides a range of measures and tools spramovannyh the financial potential of the company and adapt to changes in the environment. Acknowledged the importance of intellectual capital as one of the main elements of the capital structure of companies. Implementation of the proposed product is according to the positioning of companies in the matrix «rate of return on intellectual capital» – «level of capital invested in the activities of the company». Also based on the data results Strategic card company to improve its condition.
Formation of financial strategy of the enterprise
Keywords: зростання підприємства; економіка знань; система збалансованих показників; стратегічна карта; strategy; financial strategy; balanced scorecard; strategy map